Immune mechanisms affected by cyclooxygenase inhibition combined with antiviral treatment in calves infected with bovine respiratory syncytial virus. - Maxim Lebedev; Paul Walsh; John W Newman; Victoria N Mutua; Heather A McEligot; Francisco R Carvallo Chaigneau; Laurel J Gershwin (PLoS ONE)
Bovine respiratory syncytial virus (BRSV) infection is a part of the bovine respiratory disease complex. This is one of the most significant problems in both the dairy and beef production sector, inflicting severe economic damage to the industry. BRSV manifests clinically as a respiratory syndrome, affecting both upper and lower respiratory tract, including bronchiolitis with dyspnea and wheezing. It has been shown previously that these symptoms caused by IL-4/IL-13 domination in the immune response are associated with an antibody isotype switch to IgE. Prostaglandin production, such as PGE2 is another factor contributing to the pathogenesis of the disease. In this work we demonstrated the effects of ibuprofen and antiviral fusion protein inhibitor (FPI) separately and combined. We showed the synergistic effect of ibuprofen in combination with FPI on antiviral effects and suppression of PGE2, resulting in improved cytoplasmic toll-like receptor recognition and humoral immune responses mediated by antimicrobial peptide in lungs. We also demonstrated a Th1/Th2 balance shift towards a Th2 response in lungs and mediastinal lymph nodes, favorable to IL-4/IL-13 responses. This shift may explain the factors contributing to higher viral loads and the lack of histopathological improvement with ibuprofen administered without FPI. Additionally, we demonstrated that endocannabinoids may play a crucial role as natural regulators of the inflammation, adaptive immune response, and resolution of the inflammatory process.